Lymphatic Programing and Specialization in Hybrid Vessels - Pawlak, John B.; Caron, Kathleen M. (Frontiers in Physiology, 2020)
Building on a large body of existing blood vascular research, advances in lymphatic research have helped kindle broader investigations into vascular diversity and endothelial plasticity. While the endothelium of blood and lymphatic vessels can be distinguished by a variety of molecular markers, the endothelia of uniquely diverse vascular beds can possess distinctly heterogeneous or hybrid expression patterns. These expression patterns can then provide further insight on the development of these vessels and how they perform their specialized function. In this review we examine five highly specialized hybrid vessel beds that adopt partial lymphatic programing for their specialized vascular functions: the high endothelial venules of secondary lymphoid organs, the liver sinusoid, the Schlemm’s canal of the eye, the renal ascending vasa recta, and the remodeled placental spiral artery. We summarize the morphology and endothelial expression pattern of these vessels, compare them to each other, and interrogate their specialized functions within the broader blood and lymphatic vascular systems.